EXPLORING THE EXPERIENCES OF ENGLISH-EDUCATED PARENTS IN SUPPORTING THEIR VERY YOUNG CHILDREN'S ENGLISH LEARNING - Mailasari, Dewi Ulya; Herwani, Suci (PIAUD Universitas Islam Negeri Sunan Kudus, 2023)
This research aims to examine the experiences of parents with an English educational background in supporting early childhood English learning. This research used a descriptive method, with the number of participants being 5 parents, with an English educational background, who had children aged 4-6 years in PAUD. Data was obtained from questionnaires sent via the Google Form platform which were analyzed descriptively. The research results show that parental support is in the form of providing various media to introduce English vocabulary, carrying out social interactions by talking with children, and creating 'family time' through watching videos and singing songs together as part of language enrichment at home even though it is not routine. in terms of time. From these findings, it is necessary for parents to be able to utilize a variety of media, increase social interaction, utilize 'family time', integrate learning into routines, develop creativity in learning, play an active role in communication, and be able to support children's language. more effective development at home.